PENGARUH MARKETING MIX DAN PERSEPSI KONSUMEN TERHADAP MINAT BELI KONSUMEN PADA HOME INDUSTRY DONAT KENTANG MADONA DI KECAMATAN UNAAHA - Welis Raldianingrat; Fitria Fitria (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
This study aims to examine and analyze empirically the Effect of Marketing Mix (X1), Consumer Perception (X2), on Consumer Buying Interest (Y) in Home Industry Potato Donut Madona in Unaaha City. The population in this study were consumers who made purchases at the Home Industry of Madona potato donuts in Unaaha City, amounting to 50 people. The analytical method used in this research is multiple linear regression analysis. The results of this study indicate that Marketing Mix and Consumer Perception have a significant effect on Consumer Purchase Interest in Home Industry of Madona Potato Donuts in Unaaha City. Marketing Mix partially has a significant effect on Consumer Buying Interest in Home Industry Madona Potato Donuts in Unaaha City. Consumer Perception has a significant effect on Consumer Buying Interest in Home Industry Madona Potato Donuts in Unaaha City.Keywords: Marketing Mix, Consumer Perception, and Buying Interest.